The Still Bay points of Apollo 11 Rock Shelter, Namibia: an inter-regional perspective. Issue 3 (3rd July 2018) - Lombard, Marlize; Högberg, Anders
ABSTRACT: Dating to roughly 80, 000 to 70, 000 years ago, components of the Still Bay technocomplex of southern Africa and their potential behavioural implications have been widely discussed. Stone points with invasive retouch, as defined over 90 years ago by Goodwin and van Riet Lowe, serve as markers for Still Bay assemblages, yet many Still Bay sites remain undated and comprehensive, comparable sets of data for their point assemblages remain unpublished. Much of the Middle Stone Age at the site of Apollo 11 in Namibia was undated until 2010, when a potential Still Bay component was announced. Although a Still Bay assemblage at Apollo 11 would represent the most northwesterly and inland expression of this technocomplex, its points have never been fully analysed. This paper presents their morphometric data and an interpretation of point-production strategies. These results are then compared with data obtained for two South African sites: Hollow Rock Shelter in the Western Cape and Umhlatuzana in KwaZulu-Natal. This comparison demonstrates that whereas there are no statistically significant differences in the morphometric data sets between the three sites, there are both similarities and differences in point-production strategies, cross-section shapes and the use of raw materials for knapping. It is suggested that these similarities and variations represent aspects of how knowledge-transfer systems and knapping conventions were followed on both intra-regional and inter-regional scales.